Graphene-edge dielectrophoretic tweezers for trapping of biomolecules. Issue 1 (December 2017) - Barik, Avijit; Zhang, Yao; Grassi, Roberto; Nadappuram, Binoy; Edel, Joshua; Low, Tony; Koester, Steven; Oh, Sang-Hyun
Abstract The many unique properties of graphene, such as the tunable optical, electrical, and plasmonic response make it ideally suited for applications such as biosensing. As with other surface-based biosensors, however, the performance is limited by the diffusive transport of target molecules to the surface. Here we show that atomically sharp edges of monolayer graphene can generate singular electrical field gradients for trapping biomolecules via dielectrophoresis. Graphene-edge dielectrophoresis pushes the physical limit of gradient-force-based trapping by creating atomically sharp tweezers. We have fabricated locally backgated devices with an 8-nm-thick HfO2 dielectric layer and chemical-vapor-deposited graphene to generate 10× higher gradient forces as compared to metal electrodes. We further demonstrate near-100% position-controlled particle trapping at voltages as low as 0.45 V with nanodiamonds, nanobeads, and DNA from bulk solution within seconds. This trapping scheme can be seamlessly integrated with sensors utilizing graphene as well as other two-dimensional materials. The capability of positioning target molecules onto the edges of patterned graphene nanostructures is highly desirable. Here, the authors demonstrate that the atomically sharp edges of graphene can be used as dielectrophoretic tweezers for gradient-force-based trapping applications.